Computational thinking skills of gifted and talented students in integrated STEM activities based on the engineering design process: The case of robotics and 3D robot modeling - Sen, Ceylan; Ay, Zeynep Sonay; Kiray, Seyit Ahmet (Thinking skills and creativity, 2021)
•STEM education based on engineering design (EDP) is supported for providing an effective learning environment for and activating the skills of gifted and talented students. However, the number of studies examining the computational skills of these students in integrated STEM activities based on the EDP seems to be limited.•This research can contribute to the existing literature by revealing how EDP-based integrated STEM activities performed with gifted and talented students improve their computational thinking skills.•This research can shed light on researchers and educators for gifted and talented students' STEM education. In this study, it is aimed to identify the computational thinking skills used by gifted and talented students in integrated STEM activities based on the EDP. The case study design, a qualitative research method, is employed in the study. The participants consist of gifted and talented students attending the Science and Arts Center. Integrated STEM activities based on the EDP were conducted over the course of ten weeks and among these activities, robotic and 3D modeling-based robot construction activities using Lego sets are addressed in the present study. The STEM activity booklet, researchers' fieldnotes, and teaching process video recordings were used as data collection tools in the study. Data that was collected was analyzed through content analysis. It was seen that gifted and talented students participating in integrated STEM activities based on the EDP make active use of critical thinking skills while providing explanations, making associations, questioning information, giving justifications, solving problems, thinking creatively, making generalizations, and attempting to convince others; as for the instances of defining problems, creating solutions, and evaluating the effectiveness of the solution, the students were observed to actively use their problem-solving skills. The detailed account provided by the study on the way robotic and 3D robot modeling activities improve the computational thinking skills of gifted and talented students contributes to the required educational support and to the existing body of literature.